Impacts of Exposure to Ambient PM10 on Hospital Outpatient Visits for Haze-Related Diseases and School Children Lung Function - Mohamad, Faridah (2002)
Rapid industrialization and urbanization in Malaysia parallels the worsening air quality in the country. Besides local pollutant emitters, external sources also contribute to aggravate the condition. Haze, or the phenomenon of high air pollution particularly PM1Q, has become an annual event due to forest fires in a neighbouring country. Exposure to high levels of particulate pollution has long been reported to be detrimental to human health. This study was conducted to determine the relationship between daily PM10 level and daily hospital outpatient visits for asthma, acute respiratory infection and conjunctivitis attended to at HKL and HTAR, Klang from January 1997 (the haze year) to June 1998. Daily air quality and health data were collected retrospectively. Asthma visits were significantly elevated during the haze months. The data were also categorized to produce appropriate contingency tables. Chi-square test revealed significant association between PM10 level and asthma and conjunctivitis, particularly after two to five days lag. A cross sectional study was performed to investigate the impact of long term exposure to ambient air pollution on the lung function of a total of 780 school children between the age of 16-19 years old in the Klang Valley and Terengganu. The respiratory symptoms were surveyed (questionnaires) and the lung function (VC, FVC and FEV1) measured using a spirometer. Despite the relatively high pollution level in the Klang Valley, the subjects recorded normal lung function values. However, the lung function values of subjects in the industrial areas of Paka and Kemaman were slightly lower and the respiratory symptoms were more prevalent. Findings from the two studies suggest that asthma and conjunctivitis are associated with PM10 level. However, the types of PM10 pollution (rural/urban/industrial) are i mportant in determining its impact on the exposed population.